Місце Вищої кваліфікаційної комісії суддів та Вищої ради правосуддя в організації роботи господарських судів - Мандичев, Д. В.; Mandychev, D. V. (Право і безпека. – 2017. – № 2 (65). – С. 43-47, 2017)
Проведено порівняльний аналіз оновленого законодавства України та чинного закону «Про судоустрій і статус суддів», виявлено зміни у правових статусах Вищої кваліфікаційної комісії суддів та Вищої ради правосуддя, визначено роль цих органів в організації діяльності господарських судів. Розмежовано повноваження Вищої кваліфікаційної комісії суддів і Вищої ради правосуддя в досліджуваній сфері.

The expediency of determining the role of the High Qualifications Commission of Judges and the High Council of Justice in the organization of the activity of general jurisdiction courts, in particular economic courts, has been substantiated. The author has conducted a comparative analysis of the updated legislation of Ukraine and the current Law “On the Judiciary and Status of Judges”; has revealed the novels in the legal statuses of the High Qualifications Commission of Judges and the High Council of Justice; has determined the role of these agencies in the organization of the activity of economic courts. The powers of the High Qualifications Commission of Judges and the High Council of Justice within the researched sphere have been differentiated. It has been argued that the main role of the High Qualifications Commission of Judges and the High Council of Justice in the organization of the activity of economic courts is to ensure the complete and timely deployment of these courts with a highly professional, competent and independent judiciary agency, ensuring compliance with the discipline, incompatibility and compliance with the requirements of the legislation while the administration of justice by the judges. At the same time, the main difference in the powers of these two agencies is that the High Qualifications Commission of Judges is the direct organizer and executor of the selection of personnel for positions of judges, carrying out a special verification for them, conducting a qualification evaluation, and on the basis of the results obtained during the implementation of these measures the High Council of Justice shall take the final decision on the appointment, dismissal, transfer, and disciplinary action of judges.

Проведён сравнительный анализ обновленного законодательства Украины и действующего закона «О судоустройстве и статусе судей», выявлены изменения в правовых статусах Высшей квалификационной комиссии судей и Высшего совета правосудия, определена роль этих органов в организации деятельности хозяйственных судов. Разграничены полномочия Высшей квалификационной комиссии судей и Высшего совета правосудия в исследуемой сфере.
Место Высшей квалификационной комиссии судей и Высшего совета правосудия в организации работы хозяйственных судов
The place of the High Qualifications Commission of Judges and the High Council of Justice in the organization of economic courts’ activities
Мандичев, Д. В. Місце Вищої кваліфікаційної комісії суддів та Вищої ради правосуддя в організації роботи господарських судів / Д. В. Мандичев // Право і безпека. – 2017. – № 2 (65). – С. 43-47.
Мандичев Д. В. "Місце Вищої Кваліфікаційної Комісії суддів та Вищої Ради Правосуддя в організації роботи господарських судів." Право і Безпека 2 (2017): 43-47.
Mandychev, D.V. (2017), “The place of the High Qualifications Commission of Judges and the High Council of Justice in the organization of economic courts’ activities” [“Mistse Vyshchoi kvalifikatsiinoi komisii suddiv ta Vyshchoi rady pravosuddia v orhanizatsii roboty hospodarskykh sudiv”], Pravo i Bezpeka, No. 2, pp. 43–47.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; господарські суди; Вища рада правосуддя; Вища кваліфікаційна комісія суддів; кадрове забезпечення; economic courts; High Council of Justice; High Qualifications Commission of Judges; staffing; хозяйственные суды; Высший совет правосудия; Высшая квалификационная комиссия судей; кадровое обеспечение